A dusty star-forming galaxy at z = 6 revealed by strong gravitational lensing. (January 2018) - Zavala, Jorge; Montaña, Alfredo; Hughes, David; Yun, Min; Ivison, R.; Valiante, Elisabetta; Wilner, David; Spilker, Justin; Aretxaga, Itziar; Eales, Stephen; Avila-Reese, Vladimir; Chávez, Miguel; et al.
Abstract Since their discovery, submillimetre-selected galaxies1, 2 have revolutionized the field of galaxy formation and evolution. From the hundreds of square degrees mapped at submillimetre wavelengths3–5, only a handful of sources have been confirmed to lie atz > 5 (refs6–10 ) and only two atz ≥ 6 (refs11, 12 ). All of these submillimetre galaxies are rare examples of extreme starburst galaxies with star formation rates of ≳1, 000 M⊙ yr−1 and therefore are not representative of the general population of dusty star-forming galaxies. Consequently, our understanding of the nature of these sources, at the earliest epochs, is still incomplete. Here, we report the spectroscopic identification of a gravitationally amplified (μ = 9.3 ± 1.0) dusty star-forming galaxy atz = 6.027. After correcting for gravitational lensing, we derive an intrinsic less-extreme star formation rate of 380 ± 50 M⊙ yr−1 for this source and find that its gas and dust properties are similar to those measured for local ultra luminous infrared galaxies, extending the local trends to a poorly explored territory in the early Universe. The star-formation efficiency of this galaxy is similar to those measured in its local analogues13, despite a 12 Gyr difference in cosmic time. This paper reports the detection of a high-redshift galaxy that may be more representative of 'normal' star-forming galaxies formed in the first billion years of the Universe than the extreme starbursts discovered to date.